2023
DOI: 10.3390/biomimetics8080573
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-Containing Materials and Their Potential within New-Generation Titanium Alloys for Biomedical Applications

Rhianna McHendrie,
Wenlong Xiao,
Vi Khanh Truong
et al.

Abstract: With the rising demand for implantable orthopaedic medical devices and the dominance of device-associated infections, extensive research into the development of novel materials has been prompted. Among these, new-generation titanium alloys with biocompatible elements and improved stiffness levels have received much attention. Furthermore, the development of titanium-based materials that can impart antibacterial function has demonstrated promising results, where gallium has exhibited superior antimicrobial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Recent research has highlighted gallium’s effective antimicrobial properties without inducing cytotoxic effects [ 13 , 21 , 22 ]. Although many of the studies investigated the effect of Ga-doped materials such as glass and nanoparticle coatings rather than Ti-based systems, the antibacterial activity has nonetheless been documented [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has highlighted gallium’s effective antimicrobial properties without inducing cytotoxic effects [ 13 , 21 , 22 ]. Although many of the studies investigated the effect of Ga-doped materials such as glass and nanoparticle coatings rather than Ti-based systems, the antibacterial activity has nonetheless been documented [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has highlighted gallium’s effective antimicrobial properties without inducing cytotoxic effects [ 13 , 21 , 22 ]. Although many of the studies investigated the effect of Ga-doped materials such as glass and nanoparticle coatings rather than Ti-based systems, the antibacterial activity has nonetheless been documented [ 22 ]. For instance, Valappil et al [ 23 ] reported that Ga-doped phosphate-based glass exhibited potent antibacterial effects against five gram-negative and gram-positive bacteria strains, where even 1 mol% addition of Ga proved highly effective.…”
Section: Introductionmentioning
confidence: 99%